Chemical Tailoring of Functional Graphene‐Based Nanocomposites by Simple Stacking, Cutting, and Folding. Issue 50 (14th October 2016) - Zhang, Xiaoyan; Samorì, Paolo
Abstract : Got your work cut out : Stacking, cutting, and folding have been demonstrated to be a viable approach for the fabrication of robust nanocomposites from large‐area graphene films and polymers. This method opens up an effective route towards strong, durable, and multifunctional nanomaterials with fascinating properties.